Molecular Analysis of Eight American Type Culture Collection Gonococcal Strains by Neisseria gonorrhoeae Multiantigen Sequence Typing and PorB Sequence Typing - Chung, Yousun; Han, Minje; Park, Ji-Young; Kang, Sora; Kim, Inhee; Park, Jung A; Kim, Jae-Seok (Imsang byeong'ri wa jeongdo gwanri/Journal of laboratory medicine and quality assurance, 2019)
Background: Molecular epidemiological typing of Neisseria gonorrhoeae is crucial for monitoring the spread of resistant strains. As reference strains can be used for laboratory internal quality control, we genetically characterised the American Type Culture Collection (ATCC) gonococcal strains by Neisseria gonorrhoeae multiantigen sequence typing (NGMAST) and porB sequence typing using public multilocus sequence typing (PubMLST). Methods: Eight ATCC gonococcal reference strains (ATCC 19424, ATCC 31426, ATCC 35541, ATCC 43069, ATCC 43070, ATCC 49226, ATCC 49926, and ATCC 49981) from Culti-Loops (Thermo Fisher Scientific, USA) were cultured. After DNA extraction, porB and tbpB were amplified and sequenced. Sequence types (STs) and allele numbers were each determined by NG-MAST (http://www.ng-mast.net) and porB sequence typing using PubMLST (http://pubmlst.org/neisseria/porB/). Results: ATCC 19424 was identified as ST 266 by NG-MAST, and as Allele 946 by PubMLST. ATCC31426 was assigned a novel ST by NG-MAST, and was assigned Allele 958 with 1.2% mismatch by PubMLST. ATCC 35541 was identified as ST 12 by NG-MAST, and as Allele 624 by PubMLST. ATCC 43069 and ATCC 43070 were both identified as ST 681 by NGMAST, and as Allele 984 by PubMLST. ATCC 49226 was identified as ST 1572 by NG-MAST, and as Allele 2110 by PubMLST. ATCC 49926 and ATCC 49981 were both identified as ST 16496 by NG-MAST, and as Allele 928 by PubMLST. Conclusions: The ST data obtained for ATCC gonococcal reference strains by NG-MAST and porB sequence typing using PubMLST can be used for quality assurance of molecular epidemiological typing in clinical microbiological laboratories. KCI Citation Count: 0